Genetic profiling of virulence genes among Pseudomonas Aeruginosa isolates recovered from diseased chickens - Morsy, MM; Sorour, HK; Abdel Razek, ZS; Shalaby, AG (Journal of the Hellenic Veterinary Medical Society, 2024)
Pseudomonas aeruginosa (P. aeruginosa) is regarded as an opportunistic organism for bird species. Also is one can be mentioned as an example of an environment-associated infection that results in severe disease in poultry farms, Indeed, we detected the incidence of P. aeruginosa in chickens and also discovered the implicated virulence genes and antibiotic-resistant mechanism. Two hundred cases were collected from broiler and layer chicken organs (heart blood, heart, and lungs) that suffered from some respiratory manifestation and septicemia in addition to yolk sacs from one-day-old chicks, which were examined bacteriologically and Serologically. The studied isolates were tested against eight antimicrobial discs. Bacterial DNA was analyzed using polymerase chain reaction (PCR) against six virulence genes (lasL, lasB toxA, exoU, exoT, and oprl genes). Eighteen isolates out of 200 (9%) of P. aeruginosa were defined. Serologically the isolates were related to more serogroup (O1,O4,O6, O11 and O12) P. aeruginosa. PCR defined the existence of P. aeruginosa by detection of the 16SRNA gene. All isolates showed 100% multidrug resistance (MDR) to more than one antimicrobial disc (sulfamethoxazole, erythromycin, tetracycline, and ampicillin). Conversely, those isolates exhibited 100% sensitivity to ciprofloxacin, and four of them showed sensitivity to norfloxacin with a percentage of (22.2%). In addition to 15 isolates showed resistance of 83.3% percent to streptomycin and nalidixic acid. By PCR test, all examined P. aeruginosa strains carried four virulence genes (lasI, toxA, exoU, and oprl). However, only three strains carried lasB, and four carried the exoT gene. In conclusion, we confirmed the presence of different factors of virulence for P. aeruginosa and MDR to more than one antimicrobial drug. So, restricting Pseudomonas infection in poultry requires strict biosecurity measures to control and eradicate the infection by P. aeruginosa